Study of indoor and outdoor 1000kV GIS layout. Issue 1 (1st November 2022) - Xu, Li; Wang, Lin; Su, Guang; Xiong, Zaibao; Geng, Xiaohong; Li, Yanning
Abstract : As the backbone Grid for STATE GRID Corporation of China, UHV projects require high safety and reliability. 1000kV GIS switchgear is the most important part of UHV AC substation. Deepening the research on its layout and improving the safety and stability can provide strong technical support for the subsequent UHV AC project construction, which is of great significance. The defect and failure rate of indoor GIS is lower than that of outdoor GIS, but the initial cost of indoor GIS is higher than that of outdoor GIS layout scheme. According to the operation related data, this paper carries out the design scheme research, technical scheme comparison and life cycle analysis of indoor and outdoor layout of 1000kV GIS equipment.